Development of a baculovirus-derived chimeric virus-like particles against QX-type avian infectious bronchitis and H9N2 avian influenza - Bingchen Qiao; Qi Meng; Ni Zhao; Zihe Gao; Yusen Tian; Xifeng Hu; Chenfeng Jiang; Xiaofei Song; Jihui Ping (Veterinary Vaccine)
Currently, the spread of H9N2 avian influenza virus (AIV) and avian infectious bronchitis virus (IBV) is one of the major predicaments facing the poultry industry. Virus-like particles (VLPs)-based vaccine, as one of the most promising alternative to traditional vaccines, provides new perspectives for the prevention of poultry diseases. Here, we generated a chimeric VLPs (VLPs) vaccine against both AIV and IBV by using baculovirus/insect cell expression system, and evaluated its efficacy in chickens. The VLPs is composed of three proteins: HA, M1, and rS. The HA and M1 proteins were derived from the H9N2 AIV A/chicken/Anhui/LH99/2017 (AH/99, H9N2), while rS was composed of the S1 subunit of the QX-type IBV CK/CH/JS/CZ211063 (CZ211063, GI-19) protein and the transmembrane domain (TM) and cytoplasmic tail domain (CTD) of the H9N2 AIV HA protein. Subcutaneous immunization with the VLPs vaccine induced a robust humoral immune responses, providing complete protection against H9N2 AIV in chickens. Furthermore, challenge experiments with QX-type IBV indicated that VLPs vaccine immunization significantly inhibited viral replication in the trachea, lung, and kidney, and suppressed viral shedding in the throat and cloaca. Additionally, histopathological analysis revealed that the VLPs vaccine effectively mitigated QX-type IBV-induced tissue damages in the respiratory and renal systems. Collectively, these results suggest that the VLPs vaccine developed in this study is a promising vaccine candidate for the avian influenza and infectious bronchitis control, and highlight the potential of VLP-based vaccines as a viable alternative to traditional egg-dependent vaccines in the prevention of poultry diseases.